2011
DOI: 10.5792/ksrr.2011.23.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Single Bundle Anterior Cruciate Ligament Reconstruction by the Two Anteromedial Portal Method: The Comparison of Transportal and Transtibial Techniques

Abstract: PurposeThe purpose of this study was to report the results of anatomic single bundle anterior cruciate ligament (ACL) reconstruction by the two anteromedial portal method.Materials and MethodsWe evaluated the clinical results in 33 patients with ACL rupture who were treated by anatomic ACL reconstruction using the two anteromedial portal technique. The control group included 33 patients with ACL rupture who were treated with the conventional transtibial non-anatomic method. We performed an objective instabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 18 publications
0
35
2
Order By: Relevance
“…In the Pivot-Shift test, which analyzes the rotational stability, the anatomical technique is expected to show an advantage 19, 20, 21, 22, 23. In the present study, there were fewer cases of Pivot-Shift positivity in the outside-in technique, without statistical significance.…”
Section: Discussioncontrasting
confidence: 57%
“…In the Pivot-Shift test, which analyzes the rotational stability, the anatomical technique is expected to show an advantage 19, 20, 21, 22, 23. In the present study, there were fewer cases of Pivot-Shift positivity in the outside-in technique, without statistical significance.…”
Section: Discussioncontrasting
confidence: 57%
“…The small study size should be emphasized. Although many studies have similar case series, 6,12,[19][20][21] because it is expected that the difference of the objective and subjective outcomes is slight, large samples are necessary to detect a significant difference. Therefore, the results presented in the tables in this study should be assessed carefully because we might have type II statistical errors (i.e., not detecting a difference although it exists).…”
Section: Discussionmentioning
confidence: 99%
“…Ahn et al27) reported that remnant preserving ACL reconstruction provided good clinical outcomes and stabilities without compromising accuracy of tunnel position. However, cyclops lesions were found in 12 out of 48 patients on MRI even though they did not have any limitation in extension (Table 2)15,22,25,26,29,30). Mifune et al31) reported that remnant preserving selective bundle augmentation showed good anterior and rotational stability in patients with only AM or PL tear, and they recommended remnant preserving augmentation for partial ACL tears.…”
Section: Operative Techniques For Acl Reconstructionmentioning
confidence: 98%